DIAGNOSTIC VALUE OF SERUM N-TERMINAL PRO B-TYPE NATRIURETIC PEPTIDE (NT-PROBNP) FOR LEFT VENTRICULAR DYSFUNCTION IN HYPERTENSIVE CASES. - DSSK, RAJU; Munta, Anil Kumar; Sj, Basha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Left ventricular hypertrophy (LVH) is an independent risk factor for all cardiovascular complication of Hypertension, in this group early detection is very important for better management. Therefore, the aim of our study is to evaluate cardiac markers in hypertension with LVH. Material and Methods: The study comprised of 95 patients with the evidence of Hypertension. These cases were further divided into 2 groups i.e. Hypertension without LVH and Hypertension with LVH groups. We assessed blood pressure, electrocardiography and echocardiography. All the cardiac markers are assessed by using ELISA. Results: In the cases of LVH with hypertension group, the serum cardiac parameter like NTpro-BNP was significantly raised. However, the serum myoglobin and CK-MB did not showed any significant rise when compared with control. In the cases of LVH without hypertension, all these three parameters not have shown any significant raise when compared with control. Conclusion: Apart from imaging techniques the assessment of serum NT- pro BNP act as better marker for identifying LVH than the traditional markers like CK-MB, myoglobin. Key words: Hypertension, Left Ventricular Hypertrophy, NTpro-BNP, CK-MB and myoglobin.